2017
DOI: 10.1128/jcm.01662-16
|View full text |Cite
|
Sign up to set email alerts
|

FIND Tuberculosis Strain Bank: a Resource for Researchers and Developers Working on Tests To Detect Mycobacterium tuberculosis and Related Drug Resistance

Abstract: The spread of multidrug-resistant (MDR) tuberculosis (TB) and extensively drug-resistant (XDR) TB hampers global efforts in the fight against tuberculosis. To enhance the development and evaluation of diagnostic tests quickly and efficiently, well-characterized strains and samples from drug-resistant tuberculosis patients are necessary. In this project, the Foundation for Innovative New Diagnostics (FIND) has focused on the collection, characterization, and storage of such well-characterized reference material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…So far, there have been many well studied, conserved target regions for MTB, which include rpo B, kat G, inh A, IS6110, IS1081, etc. [16,17]. These genetic regions have also been commonly used for the development of clinical in vitro diagnostic products for MTB.…”
Section: Methodsmentioning
confidence: 99%
“…So far, there have been many well studied, conserved target regions for MTB, which include rpo B, kat G, inh A, IS6110, IS1081, etc. [16,17]. These genetic regions have also been commonly used for the development of clinical in vitro diagnostic products for MTB.…”
Section: Methodsmentioning
confidence: 99%
“…Tuberculosis (TB), caused by Mycobacterium tuberculosis, remains the most deadly infectious diseases and one of the top 10 causes of the death worldwide in 2015. Report provided by WHO showed that there are 10.4 million new cases and 1.44 million deaths in 2015, where 480,000 new cases are associated with multidrug-resistant TB (MDR-TB) with an additional 100,000 people with rifampicin-resistant TB (RR-TB) (Tessema et al 2017). The notorious tendency of M. tuberculosis with the conjunction of prolonged treatment regimens shows drug resistant which is developed in different stages (Connolly et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This intermediate range corresponds to specific mutations (e.g. gyrA A90V and D94A), whereas other mutations, such as gyrA D94G, confer higher MICs and consequently fall into the category of HLR . Such stratified pDST is already in use for INH where inhA c‐15t promotor mutations corresponding to intermediate MICs at 0.2–1 mg L −1 have been associated to favourable clinical outcomes and an increased dosing is suggested (15–20 mg kg −1 ) whereas katG S315T mutations are associated to higher MICs (>2 mg L −1 ) which cannot be overcome by increased dosing .…”
Section: Stratified Phenotypic Drug Susceptibilitymentioning
confidence: 99%